Combination of steam explosion and ionic liquid pretreatments for efficient utilization of fungal chitin from citric acid fermentation residue. (February 2021) - Ma, Qinyuan; Gao, Xiuzhen; Bi, Xinyu; Xia, Menglei; Han, Qi; Peng, Mingmeng; Tu, Linna; Yang, Yupeng; Shen, Yanbing; Wang, Min
Abstract: Aspergillus niger mycelium residues, a citric acid fermentation by-product, is a raw material for fungal chitosan and glucosamine (GlcN). However, traditional chemical extraction of fungal chitosan and GlcN uses strong acid at high temperatures for long periods and has several drawbacks, including high cost and environmental pollution. In this work, the residues were pretreated by the combination of steam explosion (SE) and ionic liquid (IL) to produce fungal chitosan and GlcN hydrochloride. Following chemical extraction, GlcN hydrochloride yield increased by 65.49 ± 8.14%, and soluble sugar release reached 0.36–0.46 g/g via SE pretreatment at 2.5 MPa for 1 min. Fungal chitosan was produced via enzymatic hydrolysis. Combined SE and IL pretreatment increased deacetylation degree (1.29 ± 0.06-fold) of fungal chitosan by chitin deacetylase hydrolysis using Rhodococcus equi CGMCC14861 (ReCDA) at 37 °C for 6 h. Besides, fungal chitosan was produced using a by-product recycling strategy, promoting ReCDA fermentation, using supernatant with soluble sugars and proteins. After mixing 0.2 g by-product supernatant with 100 mL medium, ReCDA production was 1.5-fold higher than that in the control. This study demonstrates a green technology for efficient utilization of fungal chitin from A. niger mycelium residues of citric acid fermentation. Graphical abstract: Image 1 Highlights: Aspergillus niger residue from citrate fermentation was used for chitosan production. Chitosan was produced after pretreatment of residue with steam explosion and ion liquid. Yield of sugar, chitosan deacetylation, and by-product fermentation were improved. Comprehensive utilization of A. niger waste reduced environmental pollution. Utilization of industrial waste is important for sustainable development.